"Death on Display:" Reflections on Taxidermy and Children's Understanding of Life and Death. (July 2015) - Sanders, Dawn; Hohenstein, Jill
Abstract Taxidermic collections have become perceived as extraneous in modern museums, and as such have become vulnerable to disassembly during periods of economic austerity and/or shifts in curatorial perceptions. In this paper we argue that rich educational opportunities could be lost through such actions. We highlight the ways that taxidermy provides a useful context for learning about, and understanding, the relationships between life and death in the animal kingdom. We draw attention to research on the ways taxidermic display is currently used, the ways children learn through family conversation, and the types of understandings children are known to have about life and death. We believe these collections represent potential research spaces for understanding the impact of parental communication on children's understandings of life and death. Our preliminary research plans, and conversations with curatorial partners, suggest that recording and analyzing family conversations at these sites has much to offer. Furthermore, we propose such studies might facilitate new interdisciplinary relationships between museum curators and researchers, thus contributing to wider debate on the place of natural history collections in society.